Developing rapid climate decision analysis tool in small-holder high-value crop farming in Atok, Benguet - Sonny N. Domingo; Anna Jennifer L. Umlas; Katrina Mae C. Zuluaga (Philippine Institute for Development Studies (PIDS), 2020)
Weather and climate information are useful tools for smallholder farmers to manage climate risk. The Philippine Atmospheric, Geophysical and Astronomical Services Agency, the national meteorological and hydrological agency in the Philippines, have various products that can support farmers in making decisions. However, there is a gap in access and utilization of weather and climate information. The Action ready climate knowledge to improve disaster risk management for smallholder farmers in the Philippines project aims to contribute in bridging the gap between producers and users of information. Among others, the project explores the context faced by farmers in making farm decisions that are influenced by weather and climate information. This paper discusses the data collection and initial results in developing the rapid climate decision analysis tool applicable to smallholder high value crop farming in Atok, Benguet. The excel-based tool harnesses the knowledge of farmers and agricultural extension workers and aims to aid them in decisionmaking. Information gathered are yields, production costs and prices by crop, season and amount of rainfall.
Keywords: 330; decision analysis; agriculture; smallholder farming